Pembangunan aplikasi mudah alih untuk topik perwakilan data 'JomKira" - Wan Nur Aqilah W. Yusof (Tanjong Malim, 2019)
Pembangunan aplikasi mudah alih untuk topik perwakilan data 'JomKira" by Wan Nur Aqilah W. Yusof